1998
DOI: 10.1021/ma980733s
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron Scattering Studies on Thin Films of Isotopic Polystyrene Blends

Abstract: Thin films of various thicknesses ranging from 100 µm down to 1390 Å of an isotopic polystyrene blend were examined using small-angle neutron scattering. It was found that absolute scattering data with reasonable signal-to-noise could be obtained from single films as thin as 1390 Å supported on single-crystal Si wafers by optimizing the neutron optics and by carefully eliminating background arising from the substrate. The wave vector dependence of the neutron scattering from all of the films examined could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…A comparison of these two materials is of current interest due to evidence of differences in structural features, particularly in the hydrogen distributions [4]. To optimize signal-to-noise [11,12], special c-Si substrates were used with the following specifications: float-zone wafers, 500 μm-thick (± 25 μm), undoped (resistivity>1000 Ω-cm), two-side polished with low surface roughness (<0.5 nm rms roughness, confirmed by AFM to be about 0.15 nm), (100) orientation. The wafers were diced into 2.5 cm x 2.5 cm squares to allow films to be grown with at least a 2.4-cm-diameter area to take advantage of the maximum neutron beam diameter available (2.2 cm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of these two materials is of current interest due to evidence of differences in structural features, particularly in the hydrogen distributions [4]. To optimize signal-to-noise [11,12], special c-Si substrates were used with the following specifications: float-zone wafers, 500 μm-thick (± 25 μm), undoped (resistivity>1000 Ω-cm), two-side polished with low surface roughness (<0.5 nm rms roughness, confirmed by AFM to be about 0.15 nm), (100) orientation. The wafers were diced into 2.5 cm x 2.5 cm squares to allow films to be grown with at least a 2.4-cm-diameter area to take advantage of the maximum neutron beam diameter available (2.2 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Also, weak to non-detectable signals were reported for the best quality films [5]. Recent demonstrations of good quality SANS data from very thin polymer films using signal-to-noiseenhancing conditions at the NIST Center for Neutron Research (NCNR) [11,12] encouraged us to attempt new experiments with high-quality a-Si:H. The possibility of separating out the A16.2.2 signals due specifically to the hydrogen heterogeneity (from that due, e.g., to microvoids or surface roughness) and reducing the inherently strong incoherent background scattering due to hydrogen is allowed by substituting deuterium for hydrogen [8,13,14], so we have included such samples in our first experiments as well.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 After degradation of the deuterated PMMA-co-DMEAMA porogen to form pores, there is very little neutron scattering contrast between the PMSSQ matrix and the pores. These experiments were carried out at the Center for Neutron Research at the National Institute of Standards and Technology ͑NIST͒ using the 30 m NIST-NG7 instrument.…”
Section: Methodsmentioning
confidence: 99%
“…However, the existence of such a segregated state containing 2D Gaussian globules continues to be questionable. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Very little data are available on chain conformation in strict 2D dense state. A major obstacle to resolving the problem is the lack of suitable experimental methods needed to obtain the information required for many chains in confinement of thickness comparable with a chain diameter ͑or the characteristic monomer size, a͒.…”
Section: Introductionmentioning
confidence: 99%
“…They examined local changes in chain conformation and reported a significant increase in persistent length l once the chain was confined in films of about 10 nm thickness. Kumar and co-workers [8][9][10] carried out a much broader neutron scattering investigation, covering both the Kratky and Zimm regimes, on polystyrene thin films. They showed that their data were consistent with an invariance of chain dimensions normal to the confinement direction as a function of film thickness and molecular weights.…”
Section: Introductionmentioning
confidence: 99%